PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP TINGKAT RENTABILITAS MODAL SENDIRI PADA KOPERASI WANITA TIMAH â€œKARYA RINIâ€ PANGKALPINANG - Setiawati, Epa; Makrus, Mohamad; Deseria, Rita (LPPM STIE Pertiba, 2019)
This study aims to determine the profitability value of the amount of own capital to the amount of profit to be obtained, assuming that the greater the profit, the greater the value of profitability.  The object in this study was 36